Properties of a Streptococcus salivarius spontaneous mutant in which the methionine at position 48 in the protein HPr has been replaced by a valine. - Vadeboncoeur, C (1994)
HPr is a protein of the phosphoenolpyruvate:sugar phosphotransferase system (PTS) that participates in the concomitant transport and phosphorylation of sugars in bacteria. In gram-positive bacteria, HPr is also reversibly phosphorylated at a seryl residue at position 46 (Ser-46) by a metabolite-activated ATP-dependent kinase and a Pi-dependent HPr(Ser-P) phosphatase. We report in this article the isolation of a spontaneous mutant (mutant A66) from a streptococcus (Streptococcus salivarius) in which the methionine at position 48 (Met-48) in the protein HPr has been replaced by a valine (Val). The mutation inhibited the phosphorylation of HPr on Ser-46 by the ATP-dependent kinase but did not prevent phosphorylation of HPr by enzyme I or the phosphorylation of enzyme II complexes by HPr(His-P). The results, however, suggested that replacement of Met-48 by Val decreased the affinity of enzyme I for HPr or the affinity of enzyme II proteins for HPr(His-P) or both. Characterization of mutant A66 demonstrated that it has pleiotropic properties, including the lack of IIILman, a specific protein of the mannose PTS; decreased levels of HPr; derepression of some cytoplasmic proteins; reduced growth on PTS as well as on non-PTS sugars; and aberrant growth in medium containing a mixture of sugars.